Managing VUCA through integrative self-management : how to cope with volatility, uncertainty, complexity and ambiguity in organizational behavior - Nandram, Sharda S.; Bindlish, Puneet K. (Springer, 2017)
In this book, experts discuss whether volatility, uncertainty, complexity and ambiguity (VUCA) represent a challenge or a business opportunity. More intense debates on global climate change, increased turbulence in financial quarters, increased job insecurity and high levels of stress at the workplace are attracting attention in the context of organization behavior and entrepreneurship. Fear and confusion have become part and parcel of business, often undermining trust, cooperation and inspiration. As a response, a new way of organizing self-management has emerged. The book combines practical wisdom from East and West, to develop integrative self-management theory and practice; provides direction to support an integrative mind-set, integrative organization and integrative leadership; and presents VUCA as an opportunity and necessity for development and growth, rather than a threat.
Keywords: Organizational behavior.; Management -- Employee participation.; Adjustment (Psychology); elektronické knihy; electronic books